2006
DOI: 10.1093/ecam/nek011
|View full text |Cite
|
Sign up to set email alerts
|

The Alkaloid Alstonine: A Review of Its Pharmacological Properties

Abstract: Indole compounds, related to the metabolism of tryptophan, constitute an extensive family, and are found in bacteria, plants and animals. Indolic compounds possess significant and complex physiological roles, and especially indole alkaloids have historically constituted a class of major importance in the development of new plant derived drugs. The indole alkaloid alstonine has been identified as the major component of a plant-based remedy, used in Nigeria to treat mental illnesses by traditional psychiatrists.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…19,20 The abundance and diversity of alkaloids in aerial parts of the plant may be attributed to the protective mechanism of the plant against animals and pathogens. 21 Prosopine and prosopinine alkaloids, had been reported in P. africana, 22 however, the analysis conducted by DART-MS confirmed the presence of these alkaloids in P. juliflora. Therefore, in order to verify these alkaloids and test the efficacy of DART results, they were subjected to LC/MS/MS analysis for study of their fragmentation pattern.…”
Section: Resultsmentioning
confidence: 75%
“…19,20 The abundance and diversity of alkaloids in aerial parts of the plant may be attributed to the protective mechanism of the plant against animals and pathogens. 21 Prosopine and prosopinine alkaloids, had been reported in P. africana, 22 however, the analysis conducted by DART-MS confirmed the presence of these alkaloids in P. juliflora. Therefore, in order to verify these alkaloids and test the efficacy of DART results, they were subjected to LC/MS/MS analysis for study of their fragmentation pattern.…”
Section: Resultsmentioning
confidence: 75%
“…It has been reported that the saponins show a potent sedative activity when tested in similar models (Dubois et al, 1986). Alkaloids are the most important secondary metabolites in many plants that are held responsible for their sedative and anxiolytic action (Elizabetsky and Costa-Campos, 2006). The flavonoid, hispidulin has been reported to act as a positive allosteric modulator across a range of GABA A receptor subtypes (Kavvadias et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…prevented amphetamine-induced lethality, with active doses within the range of 0. action, a complex interaction with more than one neurotransmitter system. [6] Anxiolytic and Antidepressant Properties…”
Section: Biochemical Constituentsmentioning
confidence: 99%
“…Antipsychotic therapy reduces anxiety related with mitigation of the psychosis. Alstonine possesses clear anxiolytic activity, mediated by 5-HT2A/2C serotonin receptors, suggesting effectiveness against negative symptoms of mental disorders [6] Ethyl acetate from Alstonia scholaris leaves possesses anti anxiety and antidepressant activities. The apparent mechanism was found to be selective serotonin reuptake inhibition.…”
Section: Biochemical Constituentsmentioning
confidence: 99%